Adolescence Development and the Math Gender Gap - Cristina Borra; Maria Iacovou; Almudena Sevilla (Institute of Labor Economics (IZA), 2021)
Using different production function models, we study the causal association between adolescence development and the increase in the gap in math performance between boys and girls. We use data from the 1958 British National Child Development Study, a longitudinal survey of all British children born in the first week of March 1958, containing unique information on puberty development and educational outcomes from childhood into adolescence. We first document a widening of about 10 percent of a standard deviation in the gender gap in maths from primary to secondary school in the UK, and show that adolescent development contributes to explain almost two thirds of the widening of the math gender gap during the adolescence years. We also explore the mechanisms behind these effects. Our evidence regarding differences in the impact of puberty development by age, subject and self-perceived math ability suggests that both social conditions and biological factors are behind the estimated relationships between adolescent development and the increase in the gender gap in math in secondary school.
Keywords: I21; I24; J16; 330; pubertal development; educational outcomes; gender gap in mathematics